Providing a Safe, In-Person, Residential College Experience During the COVID-19 Pandemic - Travis, Scott A.; Best, Aaron A.; Bochniak, Kristyn S.; Dunteman, Nicole D.; Fellinger, Jennifer; Folkert, Peter D.; Koberna, Timothy; Kopek, Benjamin G.; Krueger, Brent P.; Pestun, Jeff; Pikaart, Michael J.; Sabo, Cindy; et al. (Frontiers in Public Health, 2021)
Due to the COVID-19 pandemic, higher education institutions were forced to make difficult decisions regarding the 2020–2021 academic year. Many institutions decided to have courses in an online remote format, others decided to attempt an in-person experience, while still others took a hybrid approach. Hope College (Holland, MI) decided that an in-person semester would be safer and more equitable for students. To achieve this at a residential college required broad collaboration across multiple stakeholders. Here, we share lessons learned and detail Hope College's model, including wastewater surveillance, comprehensive testing, contact tracing, and isolation procedures that allowed us to deliver on our commitment of an in-person, residential college experience.